THE EFFECT OF PRODUCT AND SERVICE QUALITY ON CUSTOMER LOYALTY FORE COFFEE JABODETABEK - Anna Salsabila; Annisa Syafa Andira; Devana Dimmy Ramadhanty; Vania Olivia (Universitas Pelita Harapan, 2023)
This research is a study that aims to examine the products and services of the Fore coffee shop brand on customer satisfaction and its effect on customer loyalty. The method used in this study is a quantitative research method with a total of 30 respondents domiciled in Jabodetabek. This research method was carried out by distributing questionnaires online as well as testing validity and reliability through the Cronbach Alpha test. The results of this study show that the products and services provided by Fore Coffee are quite good, but the services provided are not too significant compared to the products offered. The results of customer satisfaction from Fore Coffee's products and services are quite visible from the products alone. The relationship between customer satisfaction and loyalty of Fore Coffee proves that products and services can increase customer loyalty. In conclusion, the products and services at Fore Cofffee are quite satisfactory and affect customer loyalty.